1987
DOI: 10.1159/000298872
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Level of Dehydroepiandrosterone Sulfate in Postmenopausal Women with Ovarian Cancer

Abstract: Serum levels of dehydroepiandrosterone sulfate (DHEAS) were measured in 41 postmenopausal women with ovarian tumor (16 with ovarian cancer, 6 with borderline malignant and 19 with benign ovarian tumor) and in 21 postmenopausal women without ovarian neoplasm. Circulating DHEAS levels were significantly lower in patients with ovarian cancer than in women with benign ovarian tumor and in control subjects. Women with advanced ovarian cancer had lower DHEAS levels than those with local ovarian cancer. An age-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Moreover, a series of epidemiological studies suggest an inhibitory effect of DHEA on various types of cancers. These epidemiological data pertain to breast cancer (281), prostate cancer (290), and ovarian cancer (291).…”
Section: Dhea and Other Cancersmentioning
confidence: 99%
“…Moreover, a series of epidemiological studies suggest an inhibitory effect of DHEA on various types of cancers. These epidemiological data pertain to breast cancer (281), prostate cancer (290), and ovarian cancer (291).…”
Section: Dhea and Other Cancersmentioning
confidence: 99%
“…In humans, low levels of DHEA and DHEAS have been regarded as a concomitance of chronic illness [ 8], malignancy [ 9], heart disease [ 10], osteoporosis [ 11], and human immunodeficiency virus (HIV) infection [ 12]. A fall in serum DHEA was considered as at least partly attributable to loss of TH1 activity in the progression from HIV positive to acquired immunodeficiency syndrome (AIDS) [ 13].…”
Section: Introductionmentioning
confidence: 99%
“…This profound age-related decline has led to investigation of the possibility that plasma levels of DHEA or DHEA metabolites may be related to the development of age-associated tumorigenesis. Case-controlled studies have shown that low serum DHEA or DHEA-S levels correlate with an increased risk of development of breast cancer in premenopausal women [49,50], ovarian cancer in postmenopausal women [51], bladder cancer [52] and gastric cancer [53]. Some studies have also shown that mean serum DHEA or DHEA-S concentrations in patients with prostate [54] and colon [55] cancer tended to be lower than those in controls.…”
Section: Physiological Roles Of Dhea In Preventing Tumorigenesis In Hmentioning
confidence: 99%